Preparation of Pendant Group-Functionalized Diblock Copolymers with Adjustable Thermogelling Behavior - Lee, Bo Keun (Polymers (Basel), 2017)
Recently, several thermogelling materials have been developed for biomedical applications. In this study, we prepared methoxy polyethylene glycol (MPEG)-b-(poly(ε-caprolactone)-ran-poly(2-chloride-ε-caprolactone) (PCL-ran-PfCL)) (MP-Cl) diblock copolymers at room temperature via the ring-opening polymerization of caprolactone (CL) and 2-chloride-ε-caprolactone (fCL) monomers, using the terminal alcohol of MPEG as the initiator in the presence of HCl. MPEG-b-(poly(ε-caprolactone)-ran-poly(2-azide-ε-caprolactone) (PCL-ran-PCL-N(3))) (MP-N(3)) was prepared by the reaction of MP-Cl with sodium azide. MPEG-b-(poly(ε-caprolactone)-ran-poly(2-amine-ε-caprolactone) (PCL-ran-PCL-NH(2))) (MP-NH(2)) was subsequently prepared by Staudinger reaction. MP-Cl and MP-N(3) showed negative zeta potentials, but MP-NH(2) had a positive zeta potential. MP-Cl, MP-N(3), and MP-NH(2) solutions formed opaque emulsions at room temperature. The solutions exhibited a solution-to-hydrogel phase transition as a function of the temperature and were affected by variation of the chloride, azide, and the amine pendant group, as well as the amount of pendant groups present in their structure. Additionally, the phase transition of MP-Cl, MP-N(3), and MP-NH(2) copolymers was altered by pendant groups. The solution-to-hydrogel phase transition was adjusted by tailoring the crystallinity and hydrophobicity of the copolymers in aqueous solutions. Collectively, MP-Cl, MP-N(3), and MP-NH(2) with various pendant-group contents in the PCL segment showed a solution-to-hydrogel phase transition that depended on both the type of pendant groups and their content.